The Relationship Between School Leaders’ Leadership Style and Contextual Factors - Nedzinskaitė-Mačiūnienė, Rasa; Stasiūnaitienė, Eglė; Česnavičienė, Juratė (Pedagogika, 2024)
The paper examines the relationship between school principals’ leadership style (adaptive, distributed, collaborative) and contextual variables. More specifically, it examines how different contextual variables (managerial seniority, size of personnel and educational institution, location, age, sex, etc.) are related to the leadership style (distributed, adaptive, collaborative) of the school leaders. For this purpose, 229 school principals from all of Lithuania took part in this quantitative research study. The results of the study show that in Lithuania, school leaders are most characterised by distributed and adaptive leadership, and least characterised by collaborative leadership. The findings from statistical analysis reveal that there is no relationship between school leaders distributed, adaptive, collaborative leadership and age, managerial seniority, or location of the educational institution. Although the study shows that school leaders are most characterised by distributed leadership, but it is not dependent on any of the contextual variables. The article introduces readers to how different contextual variables contribute to the expression of different leadership styles. The study uncovers the under researched connection between the leadership style and contextual factors in the light of COVID-19 pandemic and gives practical implications for the future.